2018
DOI: 10.20944/preprints201810.0662.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Current Situation and Future Perspectives of the Romanian Renewable Energy

Abstract: In 2015, Romania was the first country in Europe that achieved EU targets regarding the share of renewables in the generation mix, far ahead of the 2020 deadline. Starting with the energy structure in Romania, the paper: (1) analyses the evolution of the main indicators in the renewable energy sector, (2) discloses the perspectives of renewable energy in Romania synthesizing the main trends of development in the field and (3) analyses the challenges facing with the development of renewable energy in Romania. B… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Configuration R5 has growth in host-country demand as a core condition and it includes two subsidiaries in Romania from Verbund and the Czech CEZ. While CEZ is a latecomer to renewable energy, it is the largest investor in wind energy in Romania (Cîrstea et al, 2018); nearly half of its total investments went to renewables during our period of study (see Table 1). These developments reflect a shift in CEZ's corporate strategy.…”
Section: Incentive-driven Home Region-based Somnesmentioning
confidence: 99%
“…Configuration R5 has growth in host-country demand as a core condition and it includes two subsidiaries in Romania from Verbund and the Czech CEZ. While CEZ is a latecomer to renewable energy, it is the largest investor in wind energy in Romania (Cîrstea et al, 2018); nearly half of its total investments went to renewables during our period of study (see Table 1). These developments reflect a shift in CEZ's corporate strategy.…”
Section: Incentive-driven Home Region-based Somnesmentioning
confidence: 99%
“…The main advantages expected from such a PV-battery-charging station are: reduced energy demand from the grid (as power is locally generated), the energy storage reduces the negative effects of PV integration in the grid, possibilities of implementation of vehicle to home (V2H) technologies [4], [20]. Romania has met its EU targets on renewable energy generation in 2015, far ahead the 2020 target deadline, making EV charging [21] a feasible endeavor. Considering all the above, the novelty of the paper is the analysis of a proposed charging station prototype, based on a battery converter as the core component using converters widely available on the market.…”
Section: Motivationmentioning
confidence: 99%
“…Romania's energy market is not very diversified, it is dependent on gas imports from Russia, but due to the path dependence, until recently, Romania was a net exporter of electricity (Pociovalisteanu et al, 2010;Stet, 2017). But in 2018-2019 the situation changed, and today the country depends on energy imports even more than before (Cîrstea et al, 2018). Recent years proved the inefficiency of the country's electric grids, inherited from the communist past, and at the same time demonstrated that, despite this inefficiency, this is the only option for the country to start developing a new, better energy infrastructure.…”
Section: Romaniamentioning
confidence: 99%